2021
DOI: 10.3389/fmed.2021.781689
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dexmedetomidine on Postoperative Nausea and Vomiting in Adult Patients Undergoing Ambulatory Thyroidectomy: A Randomized Clinical Trial

Abstract: Background: Postoperative nausea and vomiting (PONV) is a common and disturbing problem in patients undergoing ambulatory thyroidectomy. This prospective trial aimed to explore whether dexmedetomidine (DEX) combined with azasetron (AZA) can further drop the incidence of PONV in patients undergoing ambulatory thyroidectomy compared with AZA.Methods: This single-center, randomized, double-blind trial involved 172 adult patients undergoing ambulatory thyroidectomy. The individuals were randomized to DEX + AZA gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Possible mechanism may be related to the inhibitory effect of Dex on sympathetic nerve activity, reduction in plasma catecholamine concentrations. 35 Additionally, as an adjuvant for general anesthesia, Dex can significantly reduce anesthetic consumption, which is another important factor in reducing the incidence of nausea and vomiting. Agitation during postoperative recovery is a common complication of general anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Possible mechanism may be related to the inhibitory effect of Dex on sympathetic nerve activity, reduction in plasma catecholamine concentrations. 35 Additionally, as an adjuvant for general anesthesia, Dex can significantly reduce anesthetic consumption, which is another important factor in reducing the incidence of nausea and vomiting. Agitation during postoperative recovery is a common complication of general anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that moderate use of dexmedetomidine in thyroidectomy can reduce the use of postoperative anesthesia, which will help patients’ postoperative analgesia ( 22 , 23 ). However, the use of dexmedetomidine during overnight thyroidectomy did not reduce the incidence of PONV at 24 hours in postoperation (p=0.355) ( 24 ). To reduce the incidence of the postoperative POVN, intraoperative cervical plexus anesthesia block, rational use of anesthetic drugs in preoperative multimodality, postoperative use of non-steroidal drugs such as Acetaminophen or Ibuprofen in combination with appropriate Opioid analgesia has a good effect on preventing postoperative POVN, which can also indirectly reduce the dosage of opioids ( 25 ).…”
Section: The Associated Complicationsmentioning
confidence: 99%
“…In addition, it can lead to electrolyte imbalance and extend the patient's stay in the recovery room [25]. Several studies have recently focused on the effect of dexmedetomidine on PONV, finding that it has an antiemetic effect and may reduce PONV incidence [25,26]. However, the optimal dose to achieve antiemetic effects remains unknown [18].…”
Section: Ponvmentioning
confidence: 99%